Kemampuan berpikir kritis siswa sd pada penerapan model discovery learning - Ilham Tri Mulyanto; Feny Rita Fiantika; Reza rachmadtullah (ARKA INSTITUTE, 2022)
The problem in this research is the low critical thinking ability of students and the lack of student activity in participating in learning. In learning the teacher still uses the conventional model and has not yet applied the appropriate learning model, especially for science learning. One suitable learning model is using the discovery learning model. The aim of this research is to find out whether there is an effect of discovery learning learning model on the critical thinking skills of fifth grade students on the subject of human respiratory organs at SDN Dr Sutomo V Surabaya. This research is included in a quasi-experimental research, a quasi-research is a study that provides treatment and measures the effects of treatment but does not use a random sample to conclude the changes caused by the treatment. The method used by this research is in the form of essay test questions.Based on the results of the analysis in this study, there is an influence of the discovery learning model on the critical thinking skills of the Human Breathing Organ material for the fifth grade students of SDN Dr Sutomo V Surabaya. This can be proven by using the t test formula. So it can be concluded that the discovery learning model affects the critical thinking skills of fifth grade students at SDN Dr Sutomo V Surabaya.